Pengembangan LKPD Berbantuan Android dengan Pendekatan STEM untuk Meningkatkan Keterampilan Berpikir Kritis - Aprilita Ekasari; Don Jaya Putra (Progressive of Cognitive and Ability, 2026)
Critical thinking is a basic skill needed in the 21st century. This study aims to determine the feasibility, effectiveness, influence and response of Android-assisted student worksheets with a STEM approach to improving students' critical thinking skills. The type of research used is R&D with the ADDIE type. The sample of this study used a purposive sampling technique in small-scale and large-scale trials at Muhammadiyah Merauke Middle School. Android-based worksheets are very suitable for improving critical thinking skills with an average value of V Aiken 0.84 on the critical thinking ability indicator. Android-based worksheets are effective in improving critical thinking skills with an N-Gain test score of 70.82% in the high category. 2) Android-based worksheets have an effect on improving students' critical thinking skills and creativity with a t-count value of 24.484 on the critical thinking ability indicator. Students' responses to Android-based worksheets with a STEM approach are 85% with a strongly agree category. The suggestion in this study is that Android-based worksheets with a STEM approach can help teachers change paper worksheets into interactive online worksheets. Furthermore, this Android-based student worksheet can be applied to other science materials according to students' needs. This aligns with the fact that student worksheets are quite effective in improving students' critical thinking skills and have a significant impact on t-tests